اقتصاديات الأقمار الصناعية ودورها في دعم القدرة التنافسية لقطاع الاتصالات وتكنولوجيا المعلومات في مصر - علي، محمود حسن محمد سالم (جامعة بنها - كلية التجارة, 2019)
أضحى عالم الاتصالات وتكنولوجيا المعلومات والأقمار الصناعية يتسم بكل جديد للتوجه نحو الاقتصاد المعرفي (Knowledge Economy) من ناحية ؛ وضرورة ملحة لرقى الاقتصاد القومي وازدهاره من ناحية أخري ، بالإضافة إلى العمل على زيادة ونضج الوعى المجتمعي للتقليل من الفجوة الرقمية بين المدن المصرية وكافة المناطق النائية بها ، والتي تؤثر سلبا على الإنتاجية والنمو الاقتصادي والتنمية المستدامة (Sustainable development) في ظل كافة التحديات التي تواجه الدولة في السنوات الماضية ، وسعيا وراء اللحاق بقاطرة الدول المتقدمة لتحقيق القدرة التنافسية في هذا المجال الواسع لمواجهة الآثار السلبية المترتبة على صناعة الاتصالات وتكنولوجيا المعلومات وصناعة المعدات والبرمجيات . لذلك ؛ يجب تهيئة المناخ المناسب لجذب المزيد من الاستثمارات الأجنبية المباشرة ، ومنح المزيد من الإعفاءات الضريبية للمستثمرين وتدليل كافة التحديات التي يواجهونها على المدى الطويل من اجل النمو المستدام والشمولي ، وتفعيل كافة معايير الحوكمة (Governance) لتطبيق الإصلاح المؤسسي بالدولة ، بالإضافة إلى الاعتماد على تجارب الدول المتقدمة والدول الآخذة في النمو في ظل العولمة لدعم الاقتصاد القومي، وأنشاء المشروعات الصناعية الكبيرة والمتوسطة والصغيرة ومتناهية الصغر في مجال صناعة خدمات الاتصالات وتكنولوجيا المعلومات ، وتوفير الطاقة المتجددة والطاقة الخضراء وضم العناقيد الصناعية ، بالإضافة إلى إتباع ظاهرتي الاندماج والاستحواذ للشركات غير القادرة على النهوض والتقدم وتلك بدمجها بشركات كبري وطنية أو الشركات متعددة الجنسيات للاستفادة من الخبرات والبحث والتطوير (R & D) والابتكارات بها. وللسعي وراء التطور التكنولوجي والتنمية المستدامة والارتقاء بالاقتصاد القومي؛ لابد من اتخاذ كافة التدابير اللازمة للحفاظ على المنافسة الهادفة في مجالات البحث والتطوير (R & D) والإبداع والابتكار وتكافؤ الفرص بين الجنسين، وأنشاء المشروعات التنموية، ولذلك يجب وضع استراتيجية قومية شاملة لتطوير البنية التحتية (Infrastructure) وذلك لتوفير البعد الاقتصادي الاستراتيجي الشمولي لكافة دول العالم والتوسع في التجارة الإلكترونية الأمن إلكترونيا عبر القارات. بالإضافة إلى إنشاء المدن التكنولوجية في جميع أنحاء الدولة بتفعيل دور التكتلات البشرية من الشباب والكوادر المتخصصة في التعليم العالي والفني لصناعة تلك الخدمات وصناعة وانتشار تكنولوجيا العرض والذكاء الاصطناعي والنانو تكنولوجي مع تهيئة المناخ التشريعي والقانوني الذى يحمى تلك الصناعات لجذب الاستثمارات الأجنبية المباشرة (Foreign direct investment) ودعم الصناديق الحكومية والخاصة والمشاركة الفعالة والجادة بين القطاعين العام والخاص ومنظمات المجتمع المدني، وتحقيق التنسيق من خلال التعامل الإلكتروني لشبكات القيمة المضافة ، وبالتالي النفاذ للأسواق الخارجية وتحقيق الرفاهية الاقتصادية.
The world of communications, information technology and satellites is characterized by a new orientation towards the knowledge economy on the one hand, and an urgent need for the national economy and prosperity on the other hand, in addition to working to increase and mature community awareness to reduce the digital divide between Egyptian cities and all remote areas, On productivity, economic growth and sustainable development in light of all the challenges facing the country in the past years and in pursuit of Behind the challenge of developing countries to achieve competitiveness in this wide field to counter the negative effects of the telecommunications industry, information technology and the hardware and software industry. Therefore, the appropriate climate should be created to attract more foreign direct investment, to grant more tax exemptions to investors and to overcome all the challenges they face in the long run for sustainable and inclusive growth, and to activate all standards of governance to implement institutional reform in the country. To grow under globalization to support the national economy, to establish large, medium, small and micro enterprises in the ICT industry, to provide renewable energy and For green energy and the integration of industrial clusters, in addition to following the merging and acquisition phenomena of companies that are unable to advance and progress by merging them with major national companies or multinational companies to benefit from (R & D) expertise and innovation. To pursue technological development, sustainable development and national economy, all necessary measures must be taken to maintain meaningful competition in the fields of (R & D), innovation, innovation, gender equality and the establishment of development projects. To provide the overall strategic economic dimension of all countries of the world and the expansion of electronic commerce electronically across continents. In addition to the establishment of technological cities throughout the country by activating the role of human clusters of young people and specialized cadres in higher and technical education for the manufacture of these services and the manufacture and spread of supply technology and artificial intelligence and nanotechnology with the creation of the legislative and legal environment that protects these industries to attract foreign direct investment (IDE) Governmental and private sectors and the active and serious participation of Al Qata Public and private organizations and civil society organizations (ONG), and achieve coordination through the electronic treatment of value-added networks, and thus access to external markets and economic prosperity.
Keywords: الأقمار الصناعية -- القدرة التنافسية -- تكنولوجيا المعلومات -- خدمات الاتصالات -- مصر